Analysis of Pressure Drop in Gas–Solids Cyclone Separators: An Experimental Approach - Abdallah Algoud; Abdel Salam Daleef; Belkasem Alaeuj (AlQalam Journal of Medical and Applied Sciences, 2024)
In industrial operations, cyclone separators are essential for removing particles from gas streams. The performance and energy efficiency of these devices are greatly impacted by the pressure drop across them. Through experimental investigation, this paper examines the pressure decrease in gas-solids cyclone separators. The effect of many operational factors on the pressure drop was investigated, including gas velocity, particle size, and input design.The findings demonstrated that the pressure drop across the cyclone increases significantly with increasing inflow velocity and reduces with increasing cyclone size. Regardless of cyclone size, input velocity, or particle size, a strong direct correlation was found between the pressure drop for dusty air and that for clean air. Operating at moderate gas velocities was shown to significantly reduce pressure drop without compromising separation performance, whereas higher velocities necessitate advanced cyclone designs or secondary systems to mitigate the associated pressure increases في العمليات الصناعية، تُعد فواصل الإعصار ضرورية لإزالة الجسيمات من تيارات الغاز. يتأثر أداء هذه الأجهزة وكفاءتها في استهلاك الطاقة بشكل كبير بانخفاض الضغط عبرها. من خلال التحقيق التجريبي، يبحث هذا البحث في انخفاض الضغط في فواصل الإعصار للغاز والمواد الصلبة. تم دراسة تأثير العديد من العوامل التشغيلية على انخفاض الضغط، بما في ذلك سرعة الغاز وحجم الجسيمات وتصميم المدخل. أظهرت النتائج أن انخفاض الضغط عبر الإعصار يزداد بشكل كبير مع زيادة سرعة التدفق الداخل ويقل مع زيادة حجم الإعصار. بغض النظر عن حجم الإعصار أو سرعة التدفق الداخل أو حجم الجسيمات، وُجدت علاقة مباشرة قوية بين انخفاض الضغط للهواء المحمل بالغبار وانخفاض الضغط للهواء النظيف. تبين أن التشغيل بسرعات غاز معتدلة يقلل بشكل كبير من انخفاض الضغط دون التأثير على أداء الفصل، في حين أن السرعات العالية تتطلب تصميمات إعصارية متقدمة أو أنظمة ثانوية للتخفيف من زيادات الضغط المرتبطة بذلك